ULTURALLY SUSTAINING PEDAGOGY AS COMMUNITARIAN LEGAL PLURALISM: DECOLONIZING CITIZENSHIP EDUCATION IN MULTICULTURAL NATIONS - Berebon, Charles (Universitas Negeri Makassar, 2025)
This paper proposes a radical reconceptualization of citizenship education through the theoretical integration of Culturally Sustaining Pedagogy (CSP) and Communitarian Legal Pluralism (CLP). It argues that standard civic education curricula in multicultural nations function as a form of epistemological imperialism, imposing state-centric legal monism while erasing the plural legal and normative worlds of Indigenous, religious, and ethnic minority communities. Drawing on case studies from Canada, Bolivia, and Nigeria, this research demonstrates how a CSP-CLP framework can transform citizenship education from a tool of assimilation into a platform for legal pluralism. The paper examines how CLP’s core tenets—participatory governance, moral embeddedness, and collective well-being—provide the philosophical foundation for a decolonial approach to civics that recognizes multiple, coexisting sources of legal authority and civic identity. Through analysis of existing educational experiments and theoretical synthesis, we develop a model for